(3GdOQ GdfajS hGdfhQ GdCfjS aj efGbH GdEeGe EOQjSs - (3SQGL GdOjf CHh GdYHGS CMeO Hf YHO GdMj GdMdHj GdaGSj,J (B1120 (3g` s ((3eMeO GdeCehf Hf YeQ GdEOQjSj , GdoeTJgQ HGdcJGfj s)
(3ChdgG (B:s
(3GeG HYO deG hdYJ HHjJ WjH GdPcQ GdMeOj YdbJ Hg faSj GdYGTbI (B[(3h(B] (3SejJg HGdOQ GdfajS hGdfhQ GdCfjS ai efGbH EOQjS Hf EOQjS s
(3BNQgG (B:s
(3bGd GdeDda cGf aQGZfG ef JCdja gPG GdcJGH GdeHGQc GdEOQjSj jhe GdCQHYGA GdehGab YTQjf ef QHjY GdKGfj SfI KeGf hJSYjf hCda s
(3fSNI KGfjIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B263s
(3HQhcdeGf edMb (B- (3GdLRA (B2 - (3U (B684 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B169 s
Keywords: (3GdJGQjNs